Pain after External and Endonasal Septorhinoplasty—A Propensity Score Matching Analysis - Gostian, Magdalena; Loeser, Johannes; Heindl, Ludwig; Gostian, Antoniu Oreste (Facial Plastic Surgery, 2020)
Guidelines for pain management following septorhinoplasty are lacking, leading to a wide range of therapy regimes even including opioid medication. Thus, the presented study strived to investigate and compare postoperative pain intensities after external and endonasal septorhinoplasty and evaluate whether pain perception is potentially related to patient satisfaction with the aesthetic result. In addition, the effectiveness of an escalating pain treatment protocol was evaluated sparing the necessity of opioid medication. This retrospective study performed at a tertiary referral medical center includes two well-balanced groups of 54 patients each created by propensity score matching out of a total of 161 patients following external or endonasal functional septorhinoplasty performed by a single surgeon between October 1, 2011 and March 31, 2017. Pain intensity was assessed using the visual analogue scale (0–10) on the first three postoperative days (PODs) alongside with the evaluation of the analgesic score. Patients' self-reported outcome was measured with the Utrecht questionnaire, preoperatively, and 3 and 12 months, postoperatively. Postoperative mean pain sensations were similarly high following the external and endonasal approach (F(2;190) = 2.166, p = 0.118) followed by a linear decrease over the first three PODs (F(2;190) = 16.84, p < 0.001). Pain sensations were not related to the duration of surgery, gender, patients' age, revision surgery, and the preoperative and postoperative assessment of the nasal appearance. The consumption of metamizole (F(1,76;172,15) = 2.83, p = 0.065) and ibuprofen (F(2;196) = 1.037, p = 0.356) were similarly high regardless of the surgical approach. Accordingly, both the endonasal and the external approaches led to comparable postoperative pain intensities and analgesic scores. Pain was treated effectively using a standardized escalating pain treatment protocol sparing the administration of opioids. Pain was not related to patient satisfaction with the nasal appearance pre- and postsurgery.
Keywords: septorhinoplasty; endonasal approach; postoperative pain; patient-reported outcome; external approach